Strategi Marketing Mix untuk Meningkatkan Kunjungan Wisatawan ke Desa Wisata Nongkosawit Semarang - Jannah, Desika Nur; Muchammad Satrio Wibowo; Bram Arvianto (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Even though the tourism sector in Indonesia has shown rapid development, competition between tourist destinations is increasing. Tourist villages in big cities must be able to compete with other popular tourist destinations better known to tourists, both domestic and foreign. An effective marketing strategy is needed to increase the number of tourists visiting Nongkosawit Tourism Village. Nongkosawit Tourism Village, located in Semarang City, has extraordinary natural and cultural tourism potential. This research uses a descriptive qualitative approach, which aims to analyze marketing strategies to increase tourist visits to the Nongkosawit Tourism Village, Semarang. The data collection technique used was interviews and data collection from the Mountain Cage tourism awareness group by asking for information and data regarding the Nongkosawit tourist village. Meanwhile, the data analysis technique used is based on Miles and Hubberman's theory, namely data reduction, data presentation and conclusion.